2022
DOI: 10.47909/anis.978-9916-9760-3-6.91
|View full text |Cite
|
Sign up to set email alerts
|

Academic education data as a source for analysis of the migration process for training

Abstract: In recent years, a fact that stands out in other locations on the planet is the displacement of individuals to different areas at some point in their lives. Several causes motivate displacement. Among them, one of the main reasons for training at a high level of academic training. Given this scenario, this work aims to analyze how Brazilian academic mobility occurs through data extracted from the Lattes Platform. They were filtered after extracting the data, thus obtaining only the data relevant to the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Notable benefits include the reduction of direct and indirect costs for patients and health service providers, improvement in the hiring and retention of doctors, increased patient and health professional education and training, and better accessibility to medical care. [46][47][48][49][50] The use of telemedicine skyrocketed during the COVID-19 pandemic, but 2022 marked a plateau in many respects. continue moving forward, successful integration of remote patient monitoring with connected medical devices and sensors, and training of qualified personnel to handle this technology is required.…”
Section: Discussionmentioning
confidence: 99%
“…Notable benefits include the reduction of direct and indirect costs for patients and health service providers, improvement in the hiring and retention of doctors, increased patient and health professional education and training, and better accessibility to medical care. [46][47][48][49][50] The use of telemedicine skyrocketed during the COVID-19 pandemic, but 2022 marked a plateau in many respects. continue moving forward, successful integration of remote patient monitoring with connected medical devices and sensors, and training of qualified personnel to handle this technology is required.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the research on pair programming in higher education was carried out, focusing on evaluating the validity of the experimental research. 65 When analyzing the reviewed articles, it was found that quantitative investigations of experimental design predominate, and only one investigation was oriented towards a mixed approach (qualitative and quantitative). Pair programming can have a positive impact on student learning.…”
Section: Discussionmentioning
confidence: 99%
“…El tipo de investigación utilizada fue descriptiva correlacional, de campo con un diseño no experimental, transaccional-transversal. (9) Los resultados obtenidos permitieron establecer que entre el acompañamiento pedagógico del supervisor y el desempeño del docente hay una relación significativa muy alta lo que figura que en la medida que aumenta el valor del acompañamiento pedagógico del supervisor, la variable de desempeño docente aumenta de manera alta y significativa.…”
unclassified